2020
DOI: 10.1139/apnm-2019-0966
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets are both highly oxidized and Plin2-covered in hepatocytes of diet-induced obese mice

Abstract: Chronic high-fat diet feeding is associated with obesity and accumulation of fat in the liver, leading to the development of insulin resistance and non-alcoholic fatty liver disease. This condition is characterized by the presence of a high number of intrahepatic lipid droplets (LD), with changes in the perilipin pattern covering them. This work aimed to describe the distribution of perilipin 2 (Plin2), a LD-associated protein involved in neutral lipid storage, and perilipin 5 (Plin5), that is favoring the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the present work, we synthesized bioactive lipids that combine the therapeutic properties of n3-LCPUFA and the antioxidant properties of gallic acid in the same molecule. The study performed on mice fed an HFD to promote the onset of insulin resistance, low-grade steatosis, and obesity showed that the model succeeded in representing the conditions present in MAFLD [48,49]. The results showed that the four-week administration of DRCSO alone could improve insulin levels and the HOMA index with respect to a HFD (Figure 4d,e).…”
Section: Discussionmentioning
confidence: 92%
“…In the present work, we synthesized bioactive lipids that combine the therapeutic properties of n3-LCPUFA and the antioxidant properties of gallic acid in the same molecule. The study performed on mice fed an HFD to promote the onset of insulin resistance, low-grade steatosis, and obesity showed that the model succeeded in representing the conditions present in MAFLD [48,49]. The results showed that the four-week administration of DRCSO alone could improve insulin levels and the HOMA index with respect to a HFD (Figure 4d,e).…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have reported the association between PLIN2 and liver diseases, and its involvement in fatty liver has been reported in in vivo analysis, since PLIN2 is closely related to fat droplet accumulation in the liver. Nocetti et al (20) reported that hepatocytes from mice with NaFlD induced by a high-fat diet exhibited an increase in Plin2 expression along with highly oxidized fat droplets. Griffin et al (21) also demonstrated that diet-induced hepatic lipidosis was ameliorated in liver-specific Plin2 knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Ablation of perilipin 2 (PLIN2), the most abundant lipid droplet-associated protein in steatotic liver, protects mice from diet-induced NAFLD [ 61 ]. Reduced ITCH expression increases Perilipin 2 on lipid droplets, which in turn increases lipid droplets formation in hepatocytes [ 62 , 63 ]. In humans, high levels of Plin2 are present in sarcopenia, hepatic steatosis, atherosclerosis and some types of cancer [ 64 ].…”
Section: Discussionmentioning
confidence: 99%